Platelet-rich plasma and dextrose prolotherapy in osteoarthritis knee - Yagya Parna Vohra; Afroz Ahmed Khan; Yesh Veer Singh; Abhishek Pandey; Abhinav Srivastava; Imran Shakeel Khan; Neeraj Singh (Asian Journal of Medical Sciences, 2025)
Background: A prevalent but little-understood ailment is osteoarthritis (OA) knee. It is a typical issue in daily practice. Due to the non-reversible pathophysiology of OA, treating OA knee is difficult, and physical therapy is the cornerstone of treatment. In the literature that is currently available, no crystal-clear management protocol is given. In this modest endeavor, the role of injections of Dextrose Prolotherapy (PRL) and platelet-rich plasma (PRP) in OA of the knee joint is evaluated. Aims and Objectives: The current study was designed to establish, the role of injections of Dextrose PRL and PRP in OA of the knee joint. Materials and Methods: The total study size consisted of 99 participants who were split into three groups at random: PRP+Physical Therapy (Group A, 33 participants), Dextrose PRL+Physical Therapy (Group B, 33 participants), and Physical Therapy alone (Group C, 33 Participants). The Western Ontario McMasters University OA index (WOMAC) and knee pain scale composite score were used to assess the primary end measure, which was the change in knee-related quality of life and pain. Results: There were no significant differences in Group A’s (66.58), Group B’s (63.06), and Group C’s (64.48) baseline WOMAC scores in our study (F=1.189, P=0.3090). Group A had the lowest WOMAC score at 6 months (50.48), followed by Group B (53.70) and Group C (59.27), indicating that the effects of the treatment varied (F=7.591, P=0.0009*). The highest improvement was seen in Group A from 3 to 6 months (6.70–12.09), with substantial intergroup differences (F=81.11 at 3 months, F=154.6 at 6 months; both P<0.0001). Conclusion: Two promising treatments for knee OA are PRP and dextrose PRL. This study demonstrates that Platelet-rich plasma (PRP) and dextrose prolotherapy (PRL) offer promising, non-surgical treatments for knee osteoarthritis, alleviating symptoms and enhancing quality of life without lengthy drug regimens.